THE POTENTIAL ACTIVITY OF COMBINATION OF QUERCETIN COMPOUND WITH TURMERIC EXTRACT ENCAPSULATED BY CHITOSAN NANOPARTICLES AS ALTERNATIVE THERAPY FOR DIABETES MELLITUS: A LITERATURE REVIEW - Muhammad Rifqi Al Azim Rifqi (Jurnal Medika Hutama, 2025)
Diabetes mellitus (DM) is a metabolic disease that threatens global health today. This metabolic disorder can cause microvascular and macrovascular complications. Method: This study used a Literature Review design. The study was conducted by searching the internet using a journal search engine. The journal search engines used in this study include Pubmed, Science Direct, with the keywords: "Quercetin, Turmeric (Curcuma sp), Chitosan Nanoparticles, Diabetes Mellitus. Results: The results obtained from searching the PubMed NCBI e-resources were 961, and ScienceDirect were 815. A total of 7 articles related to the topic to be studied. Conclusion: quercetin compounds and turmeric extract can be an alternative therapy for diabetes mellitus with the help of chitosan nanoparticles as a delivery system, Keywords: Quercetin, Turmeric (Curcuma sp), Chitosan Nanoparticles, Diabetes Mellitus